Teacher Education and Regional Hegemony - Hackett, Raymond S. (Daily Express, 2004)
This article discusses the need for a regional body for certifying Caribbean teachers, as identified in a symposium on teacher education held at the St. Augustine Campus of The University of the West Indies (UWI). It makes suggestions on the requirements for undertaking and sustaining such an initiative
Keywords: Teacher certification; Caribbean; Regional agencies